Reorienting Goals in Endodontic Therapy: Pulp Revitalization, on the brink of a paradigm shift. - Ayousha Iqbal; Amna Riaz; Alia Waheed; Safi Ullah Khan; Kanza Nawadat; Sadaf Islam (Journal of the Pakistan Medical Association, 2021)
Objective: To accomplish a multidisciplinary systematic review of the various aspects of dental pulp tissue engineering, its myriad protocols, inclusive of adjuvant surgeries and at the end this review will summarize the testing methodologies of pulp vitality. Methods: Research was conducted at Army Medical college, NUMS and HITECH Dental college, Taxilla. Literature of the previous 2 years was searched up to January 2020 on PubMed, SCOPUS, MEDLINE, Cochrane and Science direct. The key words employed were “revitalization, revascularization, dental pulp and regeneration ” Result & Conclusion: Current strategies of pulpal regeneration have shown commendable success. Histological analysis of clinical trials is essential to ensure confirmatory evidence of quality of revitalization. The impact of oral factors and a long term follow up in these case is still required to produce a definitive understanding. Continuous...